A Deep Brain Dissection Protocol - Guenevere Rae; Peter Oliver; Gregory Casey; Robert Cork (Association of American Medical Colleges, 2014)
Abstract Introduction Neuroanatomy courses are being compressed (especially the laboratory hours). This protocol was created to allow students to dissect a brain in the neuroanatomy course without taking up so much time that dissection is impractical. Methods The protocol is delivered in text form and as a movie tutorial. It is short enough to fit into one neuroanatomy laboratory. The movie allows faculty and students to view the dissection steps while copying them on their own specimens. Dissection steps include structures that are hard or impossible to see on a whole or half brain. The dissection takes 45 minutes. Setup and cleanup require added time, the amount of which varies depending on the number of students in the class. Results We performed the dissection protocol with 100 medical students during a 1-hour neuroanatomy lab. Using a tool that had been validated for content and reliability (internal consistency), we assessed students' depth of knowledge of neuroanatomy prior to and after using the protocol. The results revealed that upon entering the dissection session, students had an uneven knowledge base of neuroanatomy. Anatomic structures easily seen on a whole and/or half brain were correctly identified significantly more often than deep brain structures. After completing the dissection exercise, students' scores increased significantly (p < .001) due to an increase in the number of deep brain structures correctly identified rather than to any change in the number of surface brain structures correctly identified. Students' postactivity assessment showed no difference in their ability to identify the two classes of brain structures. Essentially, the dissection exercise seems to have brought students' knowledge base of deep brain structures up to the level of surface brain structures that they had acquired from the previous laboratory class session. Discussion Most of the dissection is performed with the hands, but it is helpful to have a scalpel and large knife on hand as well. For faculty and students who do not have a brain specimen, the exercise of finding these structures on a plastic model may have educational value. In addition, previous studies have shown that clay modeling can be an effective three-dimensional exercise. While watching the dissection protocol, a student could build up a brain model out of clay instead of dissecting a brain.